O escritor numa casca de noz: Lima Barreto e Osman Lins nas trincheiras do campo literário - Nunes, Bruna Fontenele (2017)
The reader can find on Guerra sem testemunhas (1969) the lines that compose Osman Lins´ writing. Those lines seem to indicate a simulated truth, inside the Avalovara (1973) author´s literary project, which is, the irreparable loneliness that comes from those who express themselves through the word. The inability to communicate becomes, then, necessary condition in the writing business. Similarly to what Foucault tell us about the insane speech, the writer´s speech needs to find itself disassociated from that language which reins the immediate life, that legitimate the consecutive actions directed to useful means, and employ a battle which only glory is, maybe, keeping the dignity. About this choice, there is an incontestable similarity between the moral imperatives that justify two fictionists, apparently radically different from each other: Osman Lins e Lima Barreto. This work has as its goal to analyze the congruencies between those two authors´ writing on which they seemed to meet, without leaving at side those aspects that last and shine in each writing. To achieve this goal, we arm ourselves with the reflections that come from philosophers and literary critics that came before us, such as: Jean-Paul Sartre, Pierre Bourdieu, Antonio Candido, Roland Barthes, Gaëtan Picon, Michel Foucault, Étienne de La Boétie, José Murilo de Carvalho, Nicolau Sevcenko, Leyla Perrone-Moisés, and many others. The first chapter of this dissertation presents a brief debate about the motivations and the discussions between those authors inside the literary field, having as background the argumentative lines from the Guerra sem testemunhas author, Osman Lins. At this stage, we observe the literary field´s peculiarities, in relation to other fields of power, to, shortly thereafter, investigate the Brazilian literary field. From the understanding of the rules of the “field”, exhaustively acquired by Pierre Bourdieu, on his As regras da arte (1992), we question the position occupied by some notable writers from the begins of the last century, to identify Lima Barreto e Osman Lins´ trenches. The second chapter reacquires the Sartre´s concept of negativity to clarify how Lima Barreto´s option for an engaged language directed him to an irreversible loneliness, transmuted in his fiction. Before realizing the hermeneutic job of Vida e morte de M.J. Gonzaga de Sá (1919), we concede to the reader a scenery that makes it possible to see the carioca fictionist´s literary project essentials. Through the acknowledgment of those pieces, we take the reasons that made Barro´s writing a representation of the contradictions of his time. The third chapter is dedicated to the meeting between those authors. As we did in the second chapter, we evaluate and debate Osman Lins´ literary project, at his phase before Nove, Novena (1966), work that signs his break from the traditional narratives, highlighting how the personal mythologies from the Pernambuco´s author helped to build his writing. The romance, which is the object of our studying and interpretation, is O fiel e a pedra (1961). About this narrative, Bernardo Cedro fights against Nestor´s tirany, similarly to Osman Lins, who, at many opportunities, refused to give in to the resources enjoyed by those inside and outside the literary power. Our main goal is to survey the unsuspected similarities between Osman Lins e Lima Barreto.